Automotive Engines Automotive Mechanics I: 9043.03. - Dade County Public Schools, Miami, FL.; Dade County Public Schools, Miami, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This automotive engines course studies and demonstrates the theory and principles of operation of the automotive four stroke cycle engine. The student will develop an understanding of the systems necessary to make the engine perform as designed, such as cooling, fuel, ignition and lubrication. This is a one or two quinmester credit course of 45 clock hours. It is the third course in the tenth grade. Included in this course is an introduction to the theory of operation of the internal combustion engine. Part of this document includes a course outline and a seven page section of post tests. (DS)
ERIC Note: An Authorized Course of Instruction for the Quinmester Program.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Auto Mechanics; Course Content; Course Objectives; Curriculum Guides; Job Skills; Performance Criteria; Power Technology; Technical Education; Trade and Industrial Education; Quinmester Program; Florida; Guides, General